1990
DOI: 10.1104/pp.94.4.1763
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Indole-3-Acetic Acid during Gravitropism in Intact Maize Coleoptiles

Abstract: We have investigated the transport of tritiated indole-3-acetic acid (IAA) in intact, red light-grown maize (Zea mays) coleoptiles during gravitropic induction and the subsequent development of curvature. This auxin is transported down the length of gravistimulated coleoptiles at a rate comparable to that in normal, upright plants. Transport is initially symmetrical across the coleoptile, but between 30 and 40 minutes after plants are tumed horizontal a lateral redistribution of the IAA already present in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
39
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 17 publications
3
39
0
Order By: Relevance
“…Went (2) and Cholodny (3) could show that this substance, called auxin, is laterally translocated in photostimulated coleoptiles, resulting in a curvature of the plant toward the light source. Using radioactively labeled auxin, Parker and Briggs (4) and Iino (5) confirmed the Cholodny-Went hypothesis (6). Whereas lateral auxin translocation in photostimulated maize seedlings is restricted to the tip (7), auxin redistribution in gravistimulated seedlings occurs along the length of the entire coleoptile (8).…”
mentioning
confidence: 85%
“…Went (2) and Cholodny (3) could show that this substance, called auxin, is laterally translocated in photostimulated coleoptiles, resulting in a curvature of the plant toward the light source. Using radioactively labeled auxin, Parker and Briggs (4) and Iino (5) confirmed the Cholodny-Went hypothesis (6). Whereas lateral auxin translocation in photostimulated maize seedlings is restricted to the tip (7), auxin redistribution in gravistimulated seedlings occurs along the length of the entire coleoptile (8).…”
mentioning
confidence: 85%
“…Recent results using modern techniques have supported this theory, including asymmetrical distribution of polar auxin transport carriers (Bennett et al, 1996;Chen et al, 1998;Friml et al, 2002) and molecular evidence for auxin asymmetry following gravity stimulation Muday et al, 1995;Lomax, 1997;Long et al, 2002;Ottenschlager et al, 2003). Lateral redistribution of radiolabeled indole-3-acetic acid (IAA) has been measured in both shoots (Parker and Briggs, 1990) and roots (Young et al, 1990;Young and Evans, 1996), and the redistribution of IAA has been shown to precede differential growth (Parker and Briggs, 1990). Other plant hormones, specifically brassinosteroids (Kim et al, 2000), ethylene (Lee et al, 1990;PhilosophHadas et al, 1996;Madlung et al, 1999), cytokinin (Golan et al, 1996), and gibberellic acid (Moore and Dickey, 1985;Rood et al, 1987;Brock and Kaufman, 1988;Chaban et al, 1999) have been shown to also play a role in gravitropism.…”
mentioning
confidence: 86%
“…The Cholodny-Went hypothesis, originally proposed in 1937, suggests that lateral transport of auxin across gravity-stimulated shoots may cause differential gravitropic growth (Evans, 1991;Trewavas, 1992). Lateral redistribution of radiolabeled indole-3-acetic acid (IAA) has been measured in both shoots (Parker and Briggs, 1990) and roots (Young et al, 1990), and the redistribution of IAA has been shown to precede differential growth and the gravity response (Parker and Briggs, 1990). Additionally, inhibition of auxin transport blocks root gravitropism (Muday and Haworth, 1994).…”
mentioning
confidence: 99%